CHARTING NEW WATERS: EVALUATING THE ROLE OF REMOTE PATIENT MONITORING TECHNOLOGY IN ENHANCING CHRONIC DISEASE MANAGEMENT BY COMMUNITY HEALTH NURSES - Majed sharar ayed Al- Harthi; Muneera Hasheem Al-Otaibi; Hanan Hasemhe Al-Otaibi; Nouf khaled AlHarthy; Abeer Hassan Alhothali; Manal saleem Rizq Allah Almuwalld; Fatmah Ahmad Alzahrani; Ghaiah Mohammad Alasmary; Hisham Khader Alyasi; Abdullah Ateeq Awwadh Althobaiti; Najlaa Ahmad Suliman Johar; Maryam Ali Ali Kaabi; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
A significant breakthrough is the use of Remote Patient Monitoring (RPM) technology as a way of improving care for chronic patients, especially for the health nursing community. This study provides an overview of how RPM has impacted patient health outcomes and the costs that are associated with the therapy of chronic conditions, such as heart failure or diabetes. The trend of chronic diseases points to the need for novel models of healthcare delivery and RPM has emerged as the relevant tool that will allow early warning signs of health deterioration to be seen and interventions across the health care system to be targeted. We are going to use the mixed method research model that involves the combination of qualitative and quantitative analyses to assess the benefits of chronic disease management where remote readings and monitoring will be used to enhance multiple disease management systems.